Pengembangan Tes Menyimak untuk Pelajar BIPA Tingkat Pemula - Diah Ayu Puspitasari; Suyono Suyono; Titik Harsiati (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2021)
Abstract: This research and development aims to produce listening test products for entry-level of BIPA students. The test products are packaged in the form of a website that can help carry out tests during a pandemic. To achieve this goal, a development design adapted from the Research Development Research (RDR) model is used. The results of this research and development are in the form of listening test products for beginner level BIPA students that are valid and reliable, reach test takers from various countries, and are equipped with a manual that makes it easy for test users.Abstrak: Tujuan penelitian pengembangan ini adalah menghasilkan produk tes menyimak untuk pelajar BIPA tingkat pemula. Produk tes tersebut dikemas dalam bentuk website yang dapat membantu pelaksanaan tes di masa pandemi. Untuk mencapai tujuan tersebut, digunakanlah desain pengembangan yang diadaptasi dari model pengembangan Research Development Research (RDR). Hasil penelitian dan pengembangan ini berupa produk tes menyimak untuk pelajar BIPA tingkat pemula yang valid dan reliabel, menjangkau peserta tes dari beragam negara, dan dilengkapi dengan buku panduan yang memudahkan pengguna tes.